2022
DOI: 10.3390/antiox11030440
|View full text |Cite
|
Sign up to set email alerts
|

Application of Transcriptome Analysis to Understand the Adverse Effects of Hypotonic Stress on Different Development Stages in the Giant Freshwater Prawn Macrobrachium rosenbergii Post-Larvae

Abstract: Salinity is one of the important environmental factors affecting survival and growth of aquatic animals. However, the impact of low-salinity stress on M. rosenbergii post-larvae at different development stages remains elusive. Therefore, the aim of this study was to explore the underlying mechanisms of hypotonic stress at different development stages of M. rosenbergii post-larvae through transcriptome analysis and antioxidant parameters detection. The salinity of the control group was 15 psu (S15) and the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Superoxide anion has strong oxidation property. Under certain conditions, the superoxide anion can be converted into other free radicals ( 33 ). In this experiment, the pyrogallol autoxidation method was used to determine the superoxide anion.…”
Section: Resultsmentioning
confidence: 99%
“…Superoxide anion has strong oxidation property. Under certain conditions, the superoxide anion can be converted into other free radicals ( 33 ). In this experiment, the pyrogallol autoxidation method was used to determine the superoxide anion.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have indicated that probiotics regulate inflammation-related genes (such as IL-10, TNFα, TLR, etc. ), thereby enhancing the host’s immune response and resistance to environmental stress [ 63 , 64 ]. This suggests that oxidative stress, triggered by environmental stressors, may activate downstream responses in inflammation pathways, potentially accelerating tissue damage and cell apoptosis [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular responses in the gill and hepatopancreas tissues of M. nipponense in response to salinity acclimation remain unknown. Few previous studies have attempted to investigate osmotic adaptive response of estuarine crustaceans by mimicking salinity stress in laboratory environments ( Li et al, 2015 ; Hudson et al, 2018 ; Liu et al, 2022 ). In case of the oriental river prawn, 14‰ is the tolerable salinity level for normal physiological activities ( Huang Y. H. et al, 2019 ), with the gills and hepatopancreas being the core metabolic tissues and the main sites of ion transport ( Pierrot et al, 1995 ; Gao et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%